Tropes for the past : Hayden White and the history/literature debate - Korhonen, Kuisma, 1964- (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2006)
In the last decades, there has been an intense debate on the relationship between literature and historiography, often linked to the debate between "empiricists" and "postmodernists". The aim of this collective work is to address this debate, and to search for new ways of thinking and encountering the past. The key note for the book comes from Hayden White, one of the leading academic figures, whose role in launching the contemporary history/literature debate has been crucial. It is followed by three critical readings of his work, all suggesting new ways to apply or challenge his views. In othe.